Analysis of causes for not filling in the nursing evaluation sheets on patient's being admitted to hospital: a qualitative perspective - Eva María Gabaldón Bravo; Javier Gómez Robles; Miguel Ángel Fernández Molina; Manuela Domingo Pozo; María Torres Figueiras; Carolina Terrés Ruiz; Loreto Gomis García (Universidad de Alicante, 2012)
The current article analyses qualitatively the project: "Study of causes for not filling in the nursing evaluation sheets on the patient's being admitted to hospital. Different perspectives to modify behaviours". (FIS 00/1049). The project is under study by a group of hospital clinical nurses and administration nurses. Aims being 1: Examining index of nursing evaluating sheets presented. 2: Evaluating different measures to increase the so low index. The methodology shows a descriptive way to quantify the above mentioned index by means of a transversal study of the clinical histories and analysis of the prior situation. A wide range of information will be requested from professionals using the technique of a nominal group. Reasons for the principal cause: sheets not being filled in should be given priorization. Strategies of intervention to solve the problem should be then taken into consideration. A pilot unit will be firstly analysed and results will be generalized to other hospital areas. Six months later, a six-month-evaluation will be done. First item to be considered is: the official sheet provided by the Consellería de Sanitat on patient's admission to hospital. Professionals from the Hospital General Universitario de Alicante - nurses - will be secondly considered. Variables to be discussed are: administrative data, general health data, basic needs: elimination patterns, mobility, feeding, respiration, hygiene...and other needs as safety, communication, etc.